Antioxidant-mediated control of degradation and drug release from surface-eroding poly(ethylene carbonate) - Bohr, Adam; Nascimento, Thais Leite; Harmankaya, Necati; Antonino, Rayane Santa Cruz M. de Q.; Beck-Broichsitter, Moritz (Acta biomaterialia, 2020)
Surface-eroding polymers are of significant interest for various applications in the field of controlled drug delivery. Poly(ethylene carbonate), as an example, offers little control over the rate of degradation and, thus, drug release, which usually conflicts with the requirements for long-acting medications. Here, we challenged an option to decelerate the degradation of poly(ethylene carbonate) in vitro and in vivo. When polymer films loaded with distinct antioxidants (vitamins) along with the model drugs leuprorelin and risperidone were incubated in superoxide radical solution and phagocyte culture, the mass loss and drug release from the delivery vehicle was a function of the type and dose of the utilized antioxidant. Once the polymer surface was “attacked” by reactive oxygen species, the antioxidants were released on demand quenching the polymer-degrading radicals. Accordingly, specific combinations of polymer and radical scavengers resulted in controlled release medications with an extended “life-time” of one month or longer, which is difficult to achieve for poly(ethylene carbonate) in the absence of antioxidants. A comparable degradation and drug release behavior was observed when antioxidant-loaded poly(ethylene carbonate) films were implanted in rats. Furthermore, linear correlations were obtained between the mass loss of the polymer films and the released fraction of drug (with slopes close to 1), a clear indication for the surface erosion of poly(ethylene carbonate) in vitro and in vivo. Overall, an addition of antioxidants to poly(ethylene carbonate)-based controlled drug delivery vehicles represents a reasonable approach to modify the performance of long-acting medications, especially when a “life time” of weeks to months needs to be achieved. Surface-eroding poly(ethylene carbonate) (PEC) is of significant interest for long-acting injectable formulations. However, PEC offers only little control over the rate of degradation and, thus, drug release kinetics. We describe an option to decelerate the degradation rate of PEC in vitro and in vivo. When polymer films loaded with distinct antioxidants along with model drugs were incubated in superoxide radical solution, phagocyte culture and implanted in rats, their mass loss and drug release was a function of the type and dose of the utilized antioxidant. Accordingly, specific combinations of polymer and radical scavengers resulted in controlled release medications with an extended “life-time” of one month or longer, which is difficult to achieve for PEC in the absence of antioxidants. Once a PEC-based drug delivery vehicle is approached by e.g., phagocytes, which secret radicals to degrade the polymer, an on-demand release of the encapsulated antioxidant took place. Consequently, slower polymer degradation accompanied by a sustained release of co-embedded therapeutic agents was observed. [Display omitted]